Ligand-binding characteristics of feline insulin-binding immunoglobulin G - SUZUKI, Takafumi (J Vet Med Sci, 2015)
Polyclonal immunoglobulin (Ig) G autoantibodies against insulin have been identified in sera of healthy cats. We purified and fractionated insulin-binding IgGs from cat sera by affinity chromatography and analyzed affinity of insulin-binding IgGs for insulin and their epitopes. Following the passing of fraction A, which did not bind to insulin, insulin-binding IgGs were eluted into two fractions, B and C, by affinity chromatography using a column fixed with bovine insulin. Dissociation constant (KD) values between insulin-binding IgGs and insulin, determined by surface plasmon resonance analysis (Biacore™system), were 1.64e(−4) M for fraction B (low affinity IgGs) and 2e(−5) M for fraction C (high affinity IgGs). Epitope analysis was conducted using 16 peptide fragments synthesized in concord with the amino acid sequence of feline insulin by an enzyme-linked immunosorbent assay. Fractions B and C showed higher absorbance (affinity) of the peptide fragment of 10 amino acid residues at the carboxyl-terminal of the B chain (peptide No. 19), followed by peptide fragments of 6 to 15 amino acid residues of the B chain (peptide No. 8). Fraction C showed a higher absorbance to 7 to 16 amino acid residues of the B chain (peptide No. 5) compared with the absorbance of fraction B. Polyclonal insulin-binding IgGs may form a macromolecule complex with insulin through the multiple affinity sites of IgG molecules. Feline insulin-binding IgGs are multifocal and may be composed of multiple IgG components and insulin.